PENGARUH SINISME ORGANISASI TERHADAP KINERJA KARYAWAN PERAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - risgiyanti risgiyanti (Neraca, 2015)
Organization cynicism was currenty an important topic in the acdemic Community as well as business but the related research was relatively neglected.Several researches that had tested the impact of organizational cynicism still showed different result.This research tested the impact of organizational cynicism especially affective cynicism about the performance by using the role of several mediator variables such as job satisfaction ,affective commitmen,continuance commitment ,and normative commitment. The data were taken from manager and employe of 23 BTM Primer member of pusat KJK syariah BTM jawa tengah.The sample of this research were 161 respondents.This research Was using survey method with quantitative approach.The tool of analysis used in the study was Partikal Least Square (PLS) which used WarpPLS 3.0 program. The result showed that affective cyniscism directly affected the employee performance.Affective cyniscism had negative impact on emplayee job satisfaction,affective commitment,and normative commitment.But,the result showed that affective cynicism had no significant impact On continuance commitment .The result also showed that job satisfaction and affective commitment Partially mediated the impact of affective cynicism on employee performance.it meant organizational cynicism could reduce the level of job satisfacation and affective commitment of the employee,which then might decresed employee performance.But, continuance commitment and normative commitment had no mediating role between affective cynicism and employee performance.